2013
DOI: 10.1017/s1355770x13000636
|View full text |Cite
|
Sign up to set email alerts
|

‘If labels for GM food were present, would consumers trust them?’ Insights from a consumer survey in Uganda

Abstract: Food labelling is costly. Food labelling is often demanded with the introduction of new food products such as genetically modified (GM) food. If consumers do not have trust in the label, scarce resources are wasted. This paper investigates factors affecting the trust in food labels among Ugandan consumers. The results suggest that older, less-educated individuals of smaller household sizes and with trust in government institutions have more trust in food labels. Other factors were also found to be important. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Furthermore, the factors affecting the public trust in the policy need to be identified and investigated [41,42]. This is because, if people do not have trust in the policy enforcement, it cannot succeed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the factors affecting the public trust in the policy need to be identified and investigated [41,42]. This is because, if people do not have trust in the policy enforcement, it cannot succeed.…”
Section: Discussionmentioning
confidence: 99%
“…An important question is whether consumers trust the regulatory agencies and if they would trust labels of transgenic products. The paper by Kikulwe et al (2014b) analyzes trust in food labels and consumers’ WTP for GM bananas in Uganda. GM bananas are expected to provide substantial economic benefits if introduced (Kikulwe et al , 2014a).…”
Section: Analyzing Attitudes Marketing and Labeling Of Gm Productsmentioning
confidence: 99%
“…The public’s attitude toward GM technologies and products, which is mediated by GM food labeling, may have a significant impact on government policy formulation and investment in new GM technologies. On the one hand, GM products have been labeled to satisfy consumers’ “right to know” and choose, 9 potentially reducing asymmetric knowledge and understanding of GM technologies between producers and consumers, 10 thereby increasing consumer acceptance. On the other hand, the intense debate on GM food labeling seems to have negatively influenced the public attitudes toward GM technologies and foods in China, 11 which could further impact national decisions to develop and commercialize GM crops.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have shown that public trust in government management of GM labeling and safety assessments likely affects individuals’ attitudes toward GM labeled foods. For instance, Kikulwe et al 9 found that consumers who have more confidence in government institutions may have a 14% higher trust in GM food labeling. However, other studies conclude that individuals who believe the government implements a mandatory labeling policy for GM food are less likely to consume GM foods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation